2008
DOI: 10.1271/bbb.80208
|View full text |Cite
|
Sign up to set email alerts
|

Yak Lactate Dehydgogenase A4: Purification, Properties, and cDNA Cloning

Abstract: Lactate dehydrogenase A4 (LDH-A4) was purified for yak skeletal muscle. Michaelis constant (Km) analysis showed that yak LDH-A4 for pyruvate was significantly higher than that of cattle. cDNA cloning of LDH-A revealed two amino acid substitutions between yak and cattle. We suggest that the higher Km of yak LDH-A4 might be a result of molecular adaptation to a hypoxic environment.Key words: yak; lactate dehydrogenase A; purification; molecular adaptationThe study of molecular adaptation has long been fraught wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…This sequence encodes 478 amino acids fully identical to that of cattle. This result is consistent with many genes assayed in yaks (Zheng et al 2008), and also provides evidence for the close phylogenetic relationship between yak and cattle.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This sequence encodes 478 amino acids fully identical to that of cattle. This result is consistent with many genes assayed in yaks (Zheng et al 2008), and also provides evidence for the close phylogenetic relationship between yak and cattle.…”
Section: Resultssupporting
confidence: 88%
“…Yaks have lower intramuscular fat content than cattle (Cai and Wiener 1995). Because of the high similarity (98脕99%) in many protein sequences assayed between yak and cattle (Zheng et al 2008), yak is considered a suitable animal model to study the influences of hypoxia on production performance. Considering the functions of LPL in lipid metabolism and adipose tissue repartition, we thus cloned yak LPL gene and assayed the expression profiles of LPL mRNA and compared with cattle, in order to highlight the molecular basis of meat quality in yaks.…”
Section: Introductionmentioning
confidence: 99%
“…Jiulong yak is an important yak breed distributed in China and the biggest yak breed in bodyweight. Yaks share very high similarity (98% to 99%) with cattle in many protein sequences assayed such as LDH (Zheng et al, 2008), so it is an excellent animal model to study influences of environmental factors such as hypoxia on its performance. It is reported that permanent exposure or acclimation to severe hypoxia decreases the mitochondrial content of muscle fibers, and oxidative muscle metabolism is shifted towards a higher reliance on carbohydrates as fuel, and intramyocellular lipid stores are reduced (for review see Hoppeler et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high sequence similarity (98 to 99%) between yak and Yellow cattle in genes assayed (Zheng et al, 2008;Bai et al, 2010;Zhang et al, 2010), yak may act as a suitable animal model to study the mechanism of hypoxia adaptation. Due to the low oxygen environment, energy supply is an important aspect for studying adaptation in yaks.…”
Section: Discussionmentioning
confidence: 99%